2019
DOI: 10.1002/pc.25468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment on mechanical properties and water diffusion characteristics of jute‐polypropylene composites

Abstract: This work presents the effect of chemical treatment of short jute fibers using alkali, potassium permanganate, and silane treatment on the mechanical properties of jute‐polypropylene (PP) composites. The chemically treated jute fibers were compounded at 30% weight fraction with PP granules in twin‐screw extruder, and the composite pellets were later injection molded to obtain the specimens for the study. The optimum parameters for the respective chemical treatments used in this study were followed as per the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…A more superficial technique such as spraying can ensure a reduction of water absorption velocity but will not have effect on the total amount of water uptake whereas a more bulky treatment such as impregnation provide the covering of some hydroxylic groups even in the inner parts of the fiber reducing the amount of water absorbed. This is confirmed by the study of Hossen et al [74], Chandekar et al [75] and Kusmono et al [76] who found out a significant reduction in water uptake after lignocellulosic fiber impregnation with silanes for jute-coir hybrid PLA and PCL (Poly-caprolactone), jute PP and fan palm polyester composites, respectively. The mentioned studies also pointed out a meaningful improvement of fiber-matrix interface confirmed by tensile and flexural properties better than the ones of the composites produced with the raw fibers.…”
Section: Surface Treatments For Interfacial Improvementsupporting
confidence: 66%
“…A more superficial technique such as spraying can ensure a reduction of water absorption velocity but will not have effect on the total amount of water uptake whereas a more bulky treatment such as impregnation provide the covering of some hydroxylic groups even in the inner parts of the fiber reducing the amount of water absorbed. This is confirmed by the study of Hossen et al [74], Chandekar et al [75] and Kusmono et al [76] who found out a significant reduction in water uptake after lignocellulosic fiber impregnation with silanes for jute-coir hybrid PLA and PCL (Poly-caprolactone), jute PP and fan palm polyester composites, respectively. The mentioned studies also pointed out a meaningful improvement of fiber-matrix interface confirmed by tensile and flexural properties better than the ones of the composites produced with the raw fibers.…”
Section: Surface Treatments For Interfacial Improvementsupporting
confidence: 66%
“…To evaluate the amount of water absorbed by the composite in water absorption test is conducted under constrained conditions. The water absorption in natural fiber composites can occur by several mechanisms like capillary action at the interface, micro voids formed during the processing of the composites 11 . The water absorption of the fabricated composites is plotted against immersion time as shown in Figure 10A.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10B shows the diffusivity against fabricated composite and from data collected the diffusion coefficient for NJMD‐0 and NJMD‐1, NJMD‐2 and NJMD‐3 are increased by 55.03%, 89.26% and 91.83%, respectively as compared to NJMD‐0. The increase in diffusion coefficient with the increase in filler wt% is attributed to that over a period of time and the micro‐cracks are formed due to the swelling of fiber 11,27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations